Estimativa de biomassa e estoque de carbono na cultura do eucalipto por meio de sensoriamento remoto - Manzato, Caroline Lourenço (2018)
The emission of CO2 into the atmosphere through the use of fossil fuels and burning of tropical forests results in a process called the greenhouse effect. Carbon sequestration is the main natural process that opposes the greenhouse effect. To minimize the concentration of this gas in the atmosphere, it is necessary to use plants that are capable of sequestering or storing the carbon in the atmosphere. Conventional methods for estimating carbon stock in forests, such as the destructive method and the method of converting the volume of wood to carbon, are very costly and require very great effort to achieve this, especially at regional or national level, the interest in making estimates through the use of remote sensing data. The vegetation indices (IVs) NDVI, SAVI, EVI and CO2FLUX were used as a tool to estimate sequestration and carbon stock. The images of the scene used in this research were in an area planted with eucalyptus forest, located in the limits of the municipalities of Avaí, Reginópolis and Bauru, in the state of São Paulo. The objective of this research was to estimate the biomass and the carbon stock, based on the IVs for the Eucalyptus spp. Culture. By obtaining the vegetation indices, it was possible to identify that the eucalyptus stands with ages of 4 and 5 years, were able to assimilate larger amounts of carbon in relation to the other evaluated ages.